QUALITY OF SERVICE AND DEVELOPMENT OF THE DEPARTMENT'S LABORATORY - Zulkifli Zulkifli; Ahmad Yani; M. Fransazeli Makorohim; Raihanatu Binqalbi Ruzain (Jambura Journal of Sports Coaching, 2023)
Departmental laboratories at tertiary institutions act as academic supports that assist students in the learning process to improve their competence. The research objectives were to determine the level of satisfaction of laboratory users and to determine the need for laboratory development for the Department of Physical Education, Health and Recreation (Penjaskesrek), Teaching and Education Faculty (FKIP), Universitas Islam Riau (UIR). This study uses a quantitative approach to the type of survey method. The subjects of this study were all laboratory users using the total sampling technique. The sample of this research is 85 students. The data collection instrument used a questionnaire and the data analysis technique used in this study was quantitative descriptive. The results of the research on the level of user satisfaction with the Penjaskesrek majors laboratory in 2023 are included in the good category with an average acquisition of 3.41 and the results of the needs analysis show 68% of 85 respondents who considered that human resources (HR), services and availability of facilities and infrastructure as well as other programs in the laboratory as a component of the needs for the development of the Penjaskesrek majors laboratory are good or sufficient.